Incompatibility studies by high performance thinâ€layer chromatography: In case of curcumin - Shrivastava, Alankar; Sharma, Jitendra; Jain, Saurabh; Aggrawal, Kanhaiya Lal (Asian Journal of Pharmaceutics (AJP), 2014)
Curcumin[1,7â€bis (4â€hydroxyâ€3â€methoxyâ€phenyl) heptaâ€1, 6â€dieneâ€3, 5â€dione] is one of the component present in the turmeric. Curcumin has been in use for its medicinal benefits since centuries and its therapeutic potential is continuously explored through various researchers throughout the world. To investigate the interaction of curcumin with commonly used excipients such as microcrystalline cellulose, starch, colloidal silica, talc, ascorbic acid, lactose, ethyl cellulose (EC), sodium carboxymethylcellulose (Naâ€CMC), hydroxyl propyl methyl cellulose and magnesium stearate. High performance thinâ€layer chromatography (HPTLC) is commonly used technique for the determination of phytoconstituents, but its application in incompatibility studies is still not investigated. Thus, we initiated our study with HPTLC followed by Fourier transform infrared and differential scanning calorimetry. Since interaction of curcumin with ascorbic acid, EC, Naâ€CMC and Mgâ€stearate confirmed by all three techniques these four excipients should be avoided during the formulation development of curcumin. The presented study also establishes HPTLCâ€™s usefulness in such interaction studies.